2010
DOI: 10.3109/09513591003632258
|View full text |Cite
|
Sign up to set email alerts
|

Low-dose vaginal estrogens or vaginal moisturizer in breast cancer survivors with urogenital atrophy: a preliminary study

Abstract: The study aim is to evaluate the efficacy and safety of two low-dose vaginal estrogen treatments (ETs) and of a non-hormonal vaginal moisturizer in postmenopausal breast cancer survivors with urogenital atrophy. Eighteen patients receiving estriol cream 0.25 mg (n = 10) or estradiol tablets 12.5 microg (n = 8) twice/week for 12 weeks were evaluated and compared with eight patients treated with polycarbophil-based moisturizer 2.5 g twice/week. Severity of vaginal atrophy was assessed using subjective [Vaginal S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
106
1
4

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(111 citation statements)
references
References 31 publications
0
106
1
4
Order By: Relevance
“…Patients who wish to consider HT after a diagnosis of breast cancer should be informed that definitive evidence on its influence in prognosis of breast cancer is lacking. The results of observational studies (which are fraught with potential biases) [Biglia et al 2010;Manson et al 2014;Santen et al 2002;Cold et al 2015] and a recent phase II RCT (evaluating use of estradiol-releasing vaginal ring 7.5 µg/d for 12 weeks) have been reassuring with respect to safety [Melisko et al 2016]. However, a single RCT suggested that HT in breast cancer survivors may increase breast cancer recurrence or new breast cancers by 2-3-fold [Holmberg and Anderson, 2004].…”
Section: Hormone Therapymentioning
confidence: 99%
See 2 more Smart Citations
“…Patients who wish to consider HT after a diagnosis of breast cancer should be informed that definitive evidence on its influence in prognosis of breast cancer is lacking. The results of observational studies (which are fraught with potential biases) [Biglia et al 2010;Manson et al 2014;Santen et al 2002;Cold et al 2015] and a recent phase II RCT (evaluating use of estradiol-releasing vaginal ring 7.5 µg/d for 12 weeks) have been reassuring with respect to safety [Melisko et al 2016]. However, a single RCT suggested that HT in breast cancer survivors may increase breast cancer recurrence or new breast cancers by 2-3-fold [Holmberg and Anderson, 2004].…”
Section: Hormone Therapymentioning
confidence: 99%
“…Tibolone is a synthetic steroid that after absorption is rapidly converted to its active form which has weak estrogenic, progestagenic, and androgenic properties [Biglia et al 2010]. It is classified as a selective tissue estrogenic activity regulator [Indhavivadhana et al 2010;Biglia et al 2010], and has been shown to improve vaginal dryness [Nappi et al 2006;Saeideh et al 2010] and may have a favourable effect on sexual function [Modelska and Cummings, 2002].…”
Section: Tibolonementioning
confidence: 99%
See 1 more Smart Citation
“…in breast cancer survivors taking aromatase inhibitors. Due to lack of proper safety data, the available clinical experience remains controversial and requires further investigation (42,43). The clinical studies for E3 have been reviewed by Head (2).…”
Section: Treatment Of Vaginal Atrophymentioning
confidence: 99%
“…Zudem ist die Verbesserung der Symptome bei Verwendung von Befeuchtungsmitteln häufig nur von kurzer Dauer. Dies konnte in einer Studie an 26 Patientinnen, die mit Östradiol, Östriol oder Befeuchtungsmitteln behandelt wurden, gezeigt werden [3]. …”
Section: Alternativenunclassified